Pendampingan Pembuatan Bedak Tabur Biang Keringat Dari Bahan Alami Tumbuhan Sereh Di Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai Sumatera Utara - Siti Aisyah Tanjung; M. Bagas Fahriansyah; Rini Fadhillah putri; Bunga Nurhidayah; Salmi; Intan Permata Sari (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Mothers in Bingkat Village have daily activities as housewives and participate with their husbands as farmers and livestock raisers, as well as social activities in village organizations and religion, not to mention activities to improve the family economy. Making loose powder for prickly heat from natural ingredients, such as nutmeg and lemongrass or other plants around the house is very easy, requires simple tools, is inexpensive, and has economic value. The target of this activity is to provide assistance in making loose powder for prickly heat and relieve itching and redness. Based on this, it is deemed necessary to provide assistance in making loose powder for prickly heat and relieve itching. Assistance is not only for production, but also includes good product packaging and counseling on marketing products made by the Bingkat Village community. This natural loose powder product has a selling value, so it is hoped that it can increase family income and welfare.